Kavain Interference with Amphetamine Immunoassay. Issue 2 (6th December 2020) - Madhavaram, H; Patel, T; Kyle, C
Abstract: We encountered unexpected false-positive urine results in three patients for amphetamine-type substances by immunoassay (IA), measured as part of community drug prevention programs. Kavain was identified in all three urine samples by gas chromatography-mass spectrometry (GC--MS). No other potential cross-reactants were found. Kavain is a kava-lactone present in kava, a ceremonial and recreational drink derived from the roots and stems of the plant Piper methysticum . It is consumed regularly by many indigenous Pacific and Australian Aboriginal communities. Urine IA was performed on a Beckman Coulter AU480 Analyzer using cloned enzyme donor immunoassay (CEDIA) amphetamine-type substance reagent and DRI ethanol reagent. We purchased three different kava powders from local kava clubs and dissolved in ethanol, then evaporated and reconstituted in blank urine and analyzed by IA, GC--MS for amphetamine-type substances. Additionally, authentic kavain standard was also tested for cross-reactivity by IA and analyzed by GC--MS to compare the mass fragmentation pattern and retention time with the kava powder and patient specimens. The patient urine samples tested positive by CEDIA IA for amphetamines. However, when analyzed by GC--MS, they were negative for amphetamine-type but contained kavain. The kava powders and kavain standard all cross-reacted with the amphetamine IA to give falsely detected results. GC--MS did not identify any amphetamine-type compounds in any of the kava powders nor in the kavain standard. To our knowledge, this is the first report of false-positive amphetamine measurements due to kavain, a component of the kava drink, widely consumed in Oceania and Australasia.